PENERAPAN PROGRESSIVE MUSCLE RELAXATION DAN GUIDED IMAGERY DALAM MENGATASI KELUHAN NYERI PADA PASIEN KANKER YANG MENJALANI KEMOTERAPI - Wahyuna Sahmar (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2018)
Objective: This literature study aims to analyze studies of progressive muscle relaxation and imaging that are guided as complementary therapies that overcome the negative effects of chemotherapy. Methods: Search of articles and journals conducted in December 2017 using the terms or topic terms of study available on the internet. The search strategy is focused on the PUBMed and Google Scholar databases. Results: This study obtained 9 journals consisting of systematic reviews, RCTs, and experimental quasi-studyafter critical judgments. Discussion: Cancer is a health problem that increases significantly in the world today. It is the second disease that causes death in the world and the seventh in Indonesia. Although chemotherapy and radiotherapy are the most common therapy for cancer patients, it has many side effects. Conclusion: This literature study shows that PMR and GI can reduce the level of pain in cancer patients undergoing chemotherapy